Deuterium retention and erosion in liquid Sn samples exposed to D2 and Ar plasmas in GyM device. (December 2018) - Cremona, A.; Vassallo, E.; Alves, E.; Causa, F.; De Iuliis, S.; Dondè, R.; Giacomi, G.; Gervasini, G.; Granucci, G.; Iafrati, M.; Maddaluno, G.; Mateus, R.; et al.
Highlights: Liquid Sn showed a very low level of D retention. Deuterium is adsorbed on the surface of Sn samples and does not penetrate into the bulk. Effective S/XB for the Sn I line at 380.1 nm has a value of 150  ±  23 in the 5–11 eV Te range, at a density ne  ∼ 1.5 × 10 11  cm −3 . Abstract: The use of tin (Sn) as a liquid metal for plasma facing components has been recently proposed as a solution to the high heat load issue on the divertor target plates in nuclear fusion reactors. Due to its low vapor pressure, low reactivity with hydrogen and good resilience to neutron impact, tin is a good candidate as plasma facing component. However its high atomic number poses concerns about plasma contamination. In this paper two fundamental aspects have been investigated: deuterium retention and erosion fluxes from the Sn surface towards the plasma. The samples were exposed to plasma inside the linear machine GyM in magnetic cusp configuration. This setup permits to expose free liquid specimens without the need for the Capillary Porous System. Moreover it permits to lower the magnetic field in order to increase Sn Larmor radius and consequently limit Sn re-deposition in erosion experiments. Ex-situ analyses by ion beam diagnostics on solid samples exposed to deuterium plasma have proved that the amount of retained atomic deuterium is very low, approximately 0.18 at% estimated by Nuclear Reaction Analysis and 0.25 at% estimated by Elastic Recoil Detection Analysis. In the framework of erosion studies, the spectroscopic parameter S/XB was evaluated in Ar plasma for the SnI line at 380.1 nm by Optical Emission Spectroscopy and mass loss measurements in the 5–11 eV Te range, at a density ne  ∼ 1.5 × 10 11  cm −3 . An average value of 150 ± 23 was obtained.